The influence of market competition on SMEs' performance in emerging economies: Does process innovation moderate the relationship? - Solomon Abekah Keelson; Juraj Cúg; John Amoah; Zora Petráková; Jacob Odei Addo; Abdul Bashiru Jibril (Economies, 2024)
Small and medium enterprises (SMEs) are vital to the economic development of emerging economies, significantly contributing to employment, innovation, and GDP growth. This study investigates the influence of market competition on SME performance in emerging economies, specifically examining the moderating role of process innovation. Using a sample of 365 SMEs in the western region of Ghana, the research employed a convenience sampling technique to gather data. The analysis utilized partial least square structural equation modeling (PLS-SEM) to explore the relationships between market competition, process innovation, and SME performance. The findings revealed that three direct hypotheses were supported, indicating a positive relationship between market competition and SME performance, while the moderated hypotheses were not supported. These insights provide valuable implications for SME owners, managers, and policymakers.
Keywords: 330; emerging economies; innovation; market competition; SMEs